Synthesis and Cytotoxicity Evaluation of Novel C-3 Aminocarbamate Pregnenolone Derivatives - Patchanee Charoenying; Nawasit Chotsaeng (My University, 2024)
Cancer is one of the leading causes of death worldwide. There are many ongoing studies in the search for new treatments or drugs to combat cancer. Similarly, in this research, twelve 3-aminocarbamate pregnenolones (2a–2l) were designed, synthesized, and evaluated for their cytotoxicity against five cancer cell lines: Human hepatocellular carcinoma (HepG2), Human colon adenocarcinoma (HT-29), Human oral cavity carcinoma (KB), Human breast adenocarcinoma (MCF-7), Murine leukemia (P388), and one normal cell line, African green monkey kidney fibroblast (Vero), using the MTT assay. Notably, 3-aminobenzylcarbamate pregnenolone (2b), 3-diaminoheptylcarbamate pregnenolone (2f), and 3-diaminopropanolcarbamate derivative (2i) were the most potent against these cancer cell lines. Specifically, for P388 cell lines, these compounds were more potent than the positive control drug, vinblastine sulfate salt. Results from the SAR study demonstrated that the length of the alkyl chain of diaminocarbamate derivatives was crucial for their anticancer properties. These findings will be useful in the future research and development of anticancer drugs.
Keywords: MTT assay; Synthesis and Biological Evaluation